A301 ANTIBIOTICS INCREASE VAGAL AFFERENT FIRING IN THE MOUSE JEJUNUM. (1st March 2018) - Delungahawatta, T N; West, C; Stanisz, A; Bienenstock, J; Forsythe, P; Kunze, W A
Abstract: Background: Accumulating evidence from animal studies suggests antibiotics administered to the gut lumen may act directly on the host nervous system. For instance, we have previously shown that introduction of bacitracin, neomycin and penicillin V antibiotics in mouse jejunum and colon, results in short-latency changes to neurally-dependent enteric reflexes (Frontiers in Neuroscience, in press). However, it remains to be determined whether antibiotics influence neural communication pathways to the brain. Therefore, our goal was to identify antibiotic-induced shifts to vagal spike trains recorded from the jejunal mesenteric nerve bundle. Since clinical administration of antibiotics has been associated with central nervous system excitation and convulsions, we hypothesize that antibiotics may increase the discharge activity of vagal sensory afferents. Aims: To determine whether acute exposure of the gastrointestinal lumen to antibiotics modulate action potential discharge rates in vagal afferent fibres. Methods: Distal jejunal segments with attached mesenteric tissue were excised from adult male Swiss Webster mice and carefully pinned out in a recording dish. The mesenteric nerve bundle was isolated by dissection under a stereomicroscope and sucked into a glass pipette attached to a patch-clamp electrode holder (CV-7B; Molecular Devices, Sunnyvale, CA). Extracellular multi-unit neuronal activity was recorded using a Multi-Clamp 700B amplifier and Digidata 1440A signal converter (Molecular Devices) while gut lumen was perfused with control Krebs solution (containing 3μM nicardipine to prevent muscle contractions) followed by the same Krebs solution with 3 mM penicillin V. Mesenteric nerve response to CCK identified single-unit vagal activity. Paired comparisons were made for before and after treatment recordings. Differences were considered significant if p < 0.05. Results: Preliminary data show that 3 mM penicillin V significantly increased constitutive vagal firing rate by 76% (1.4 ± 0.26 to 2.1 ± 0.24 Hz, n=15(2)) within minutes of application. Conclusions: We have demonstrated antibiotic-mediated increases in intrinsic vagal afferent activity. Further in vivo studies are needed to determine whether such increases in vagal firing frequency produce changes in brain neurochemistry and behavior. Funding Agencies: Natural Sciences and Engineering Council of Canada Discovery Grant (2014–05517), and the Canadian-Israel Health Initiative jointly funded by the Canadian Institutes of Health Research, the Israel Science Foundation, the International Development Research Centre, Canada and the Azrieli Foundation (267429)